2002
DOI: 10.1007/s11606-002-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a brief teaching encounter using standardized patients

Abstract: A single, 1-hour teaching intervention lead to a 2- to 3-fold increase in resident detection and advising of problem drinkers. SPs provide effective teaching encounters and a useful measure of resident behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…12,28,29 Approximately 70% of the current sample demonstrated skills necessary for a brief intervention. This is similar to Wilk & Jenson 26 findings which reported that 74% of residents in an internal medicine clinic provided an alcohol intervention to an unannounced SP following alcohol training. The current study did not utilize a pre-post SP design.…”
Section: Discussionsupporting
confidence: 88%
“…12,28,29 Approximately 70% of the current sample demonstrated skills necessary for a brief intervention. This is similar to Wilk & Jenson 26 findings which reported that 74% of residents in an internal medicine clinic provided an alcohol intervention to an unannounced SP following alcohol training. The current study did not utilize a pre-post SP design.…”
Section: Discussionsupporting
confidence: 88%
“…One demonstrated a positive association between resident nonverbal communication skills and patient satisfaction 63 . Another documented improved resident performance with unannounced SPs 64 . Another institution documented wide variations in resident performance including making incorrect recommendations to patients on a domestic violence observed‐structured‐clinical‐evaluation (OSCE) 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Several OSCEs administered before and after educational programs demonstrated improvements in medical students’ substance abuse clinical skills (18,19). Among resident physicians, two studies used SPs to demonstrate the effect of substance abuse training on clinical skills (20,21), and one used SPs to describe the need for improvement in these skills (5,10). …”
Section: Discussionmentioning
confidence: 99%